Assessment of somatosensory changes in Chinese temporomandibular disorders arthralgia patients by quantitative sensory testing. (10th July 2020) - Wang, Yang; Zhao, Yanping; Yang, Guangju; Xie, Qiufei
Abstract: Background: Somatosensory changes in Chinese temporomandibular disorders (TMD) arthralgia patients have not been fully studied by the latest technologies. Objective: This study aims at assessing somatosensory changes in Chinese TMD arthralgia patients quantitatively. Methods: Standardised quantitative sensory testing (QST) was performed on the pain sites and contralateral sites of 40 patients diagnosed with TMD arthralgia according to the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) before and after medication; similar measures were taken in 40 age‐ and gender‐matched healthy controls. Differences within and between groups were assessed through Z ‐scores, two‐way ANOVA and loss/gain coding system. Results: The pain sites of patients presented increased sensitivity to thermal stimuli and mechanical pain stimuli together with decreased sensitivity to mechanical tactile stimuli before medication ( P < .001). Before treatment, 100% of patients had somatosensory abnormalities at the pain sites; the most frequent abnormalities were somatosensory gain to cold nociceptive, pinprick and pressure stimuli, and the most frequent loss/gain score was L0G3 (no somatosensory loss with a gain of thermal and mechanical somatosensory function; 70.0%). After treatment, although the clinical symptoms and signs of 40 patients disappeared, 80.0% of the patients' pain sites still showed multiple phenotype abnormalities. The most frequent loss/gain score was L0G2 (no somatosensory loss with a gain of mechanical somatosensory function; 35.0%). Conclusions: Multiple phenotypes of facial somatosensory abnormalities were detected in Chinese TMD arthralgia patients before and after treatment, despite the disappearance of clinical signs and symptoms. Individual variations indicate a possible need for subgroup classification, individualised management and mechanism‐based treatment.